THE FACTORS INFLUENCING THE EMPLOYEE PERFORMANCE IN PT HIKMAH SEJAHTERA SURABAYA - Mei Retno Adiwaty (Universitas Hayam Wuruk Perbanas, 2010)
In improving the employees’ performance, a company needs to realize the commitment to the improvement for the employees prosperity, quality, and leadership style in which those fac- tors are assumed to contribute to the greater interest of the company through employees’ performance and achievements. PT. Hikmah Sejahtera Surabaya is a multi-business company suffering from the performance decline almost in every business unit the company owns. Due to such a condition, this research aimed to acknowledge in-depth analysis on the influence of Compensation, Motivation, and Leadership style towards the employee performance in PT. Hikmah Sejahtera Surabaya. It uses the population consisting of the entire employees work- ing in the company that are included as the research sample. This research employed Census sampling method and SEM (Structural Equation Modeling) as its data analysis technique. The analyses led to conclusions that leadership does not influence motivation, compensation does not influence performance, and as well as the leadership. Meanwhile, compensation has significant-positive influence towards motivation and motivation has significant-positive influence towards performance. Therefore, management should pay greater concern particu- larly on the employees’ compensation policy (bonuses and benefits), thus engaging them to be highly motivated as well as to be willingly responsible and in-charge for achievement efforts.